Bacterial artificial chromosomes as recombinant reporter constructs to investigate gene expression and regulation in echinoderms. (17th October 2017) - Buckley, Katherine M; Dong, Ping; Cameron, R Andrew; Rast, Jonathan P
Abstract: Genome sequences contain all the necessary information—both coding and regulatory sequences—to construct an organism. The developmental process translates this genomic information into a three-dimensional form. One interpretation of this translation process can be described using gene regulatory network (GRN) models, which are maps of interactions among regulatory gene products in time and space. As high throughput investigations reveal increasing complexity within these GRNs, it becomes apparent that efficient methods are required to test the necessity and sufficiency of regulatory interactions. One of the most complete GRNs for early development has been described in the purple sea urchin, Strongylocentrotus purpuratus . This work has been facilitated by two resources: a well-annotated genome sequence and transgenes generated in bacterial artificial chromosome (BAC) constructs. BAC libraries played a central role in assembling the S. purpuratus genome sequence and continue to serve as platforms for generating reporter constructs for use in expression and regulatory analyses. Optically transparent echinoderm larvae are highly amenable to transgenic approaches and are therefore particularly well suited for experiments that rely on BAC-based reporter transgenes. Here, we discuss the experimental utility of BAC constructs in the context of understanding developmental processes in echinoderm embryos and larvae.